2017
DOI: 10.7287/peerj.preprints.2451v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomically-linked growth phenotypes during arsenic stress among arsenic resistant bacteria isolated from soils overlying the Centralia coal seam fire

Abstract: 23 24Arsenic (As), a toxic element, has impacted life since early Earth. Thus, microorganisms have 25 evolved many As resistance and tolerance mechanisms to improve their survival outcomes given 26 As exposure. We isolated As resistant bacteria from Centralia, PA, the site of an underground 27 coal seam fire that has been burning since 1962. From a 57.4°C soil collected from a vent above 28 the fire, we isolated 25 unique aerobic arsenic resistant bacteria spanning six genera. We 29 examined their diversity, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Finally, it is worth noticing that both arsenate reductase (codified by arrA or arsC genes) only amplified in cultures supplemented with As(III), and that the amplifications of two forms of the primers that codified for the arsenite oxidase was observed in the anaerobic culture supplemented with arsenate Ana(As 5+ 50 mM). Our results, together with other related studies, prove the need to increase the knowledge of microbial resistance mechanisms to improve the design of primers, not only for the characterization of species but, more importantly, to enable the use of specific resistance genes as markers of As environmental contamination .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Finally, it is worth noticing that both arsenate reductase (codified by arrA or arsC genes) only amplified in cultures supplemented with As(III), and that the amplifications of two forms of the primers that codified for the arsenite oxidase was observed in the anaerobic culture supplemented with arsenate Ana(As 5+ 50 mM). Our results, together with other related studies, prove the need to increase the knowledge of microbial resistance mechanisms to improve the design of primers, not only for the characterization of species but, more importantly, to enable the use of specific resistance genes as markers of As environmental contamination .…”
Section: Discussionsupporting
confidence: 66%
“…Even though our results are only preliminary, they show that in presence of As the tolerant consortia maintain acceptable µ values and reach approximately the same cellular concentrations than As‐free cultures, both desirable characteristic for the design of a bioremediation process. On this subject, it has been reported that microorganisms which develop faster might be better suited to cope with As contamination than those that present high Minimum Inhibitory Concentration (MIC) values .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently determine that, despite the fire activity at this particular site, the soil had relatively low As concentrations at the time of soil collection (2.58 ppm). This is not surprising, given that 1) the fire is dynamic and past arsenic concentrations at the vent may have been higher given the natural occurrence of As as a byproduct of coal combustion (30,32) and 2) the widespread observation of microbial As resistance from soils that have generally low contamination (39,(58)(59)(60)(61). Accordingly, all 25 isolates were rare within their soil microbial community ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…While other reports have examined growth reduction in the presence of As to find suitable strains for bioremediation(15,(60)(61)(62)(63), a suite of growth parameters are not typically investigated. Our full characterization of growth in increasing concentrations of As showed a modest relationship between growth phenotype and taxonomy and highlights discrepancies between fitness in As and MIC.…”
mentioning
confidence: 99%